PENERAPAN METODE SPEED READING TERHADAP KEMAMPUAN MEMBACA PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SD NEGERI 31 PALEMBANG - Nikmaturohmah; Misdalina; Hermansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the application of the speed reading method to reading skills in Indonesian language learning for fifth grade students at SD Negeri 31 Palembang. The type of research used by researchers is descriptive with a quantitative approach, the design used in this study is pre-exsperimental (non-designs) with the type of “pre-test and post-test one group design”, namely research using only one class without any comparison class or control class. The population and sample of this study are the population of all students from class I to class VI of SD Negeri 31 Palembang, totaling 251 people and the sample is class V, totaling 20 people. Data was collected using observation and also tests, the data collected was analyzed using pretest and posttest. The results of the study showed that the results of reading ability before being taught using speed reading reached the high category. So it can be concluded that the speed reading method can be used to improve reading skills, some of the advantages are that it can activate students during the learning process, attract students’ attention and facilitate student understanding. Keywords: Speed Reading Method, Reading Ability